Validasi Metode Penetapan Kadar Besi (Fe) dalam Telur Bebek menggunakan Spektrofotometri Serapan Atom (SSA) - Khairiyanti Khairiyanti; Handrian Syahputra Siregar (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Iron (Fe) is an essential mineral that plays a crucial role in hemoglobin formation and various biological processes in the body. Duck eggs are known to contain a relatively high iron content, making it important to determine their iron levels using an accurate and reliable analytical method. This study aimed to validate the Atomic Absorption Spectrophotometry (AAS) method for determining iron content in duck eggs available in the Banjarbaru market, South Kalimantan. Duck egg samples were analyzed using a wet digestion method before measurement with AAS at a wavelength of 248.3 nm. The validated method parameters included linearity, limit of detection (LOD), limit of quantification (LOQ), precision, and accuracy. The results showed that the calibration curve had a correlation coefficient (r) of 0.9994 and a determination coefficient (R²) of 0.9988, indicating excellent linearity in the range of 0.0–10 ppm. The obtained LOD and LOQ values were 0.08 ppm and 0.27 ppm, respectively. Precision was demonstrated by an RSD of 7,01% for repeatability and 6.94% for intermediate precision, meeting the acceptance criteria. The accuracy of the method, indicated by an average % recovery of 98,40% ± 0,84, was also within the acceptable range (80–110%). Therefore, the validated AAS method in this study can be used as an accurate and reliable approach for analyzing iron content in duck eggs.